INFORMASI YANG DIBUTUHKAN PESERTA DIDIK DALAM MEMPERSIAPKAN DIRI UNTUK MEMASUKI PRAKTEK KERJA INDUSTRI DI KELAS XI SMK NEGERI 6 PADANG - Oktaviano, Randi; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
This research is descriptive research, population of this research is all of students in class XI of SMK N 6 Padang which is totally 342 students, and sample technique of this research uses purposive random sampling. Technique of data collection is questionaire filling and data analysis used is percentase technique, it is to describe information which is needed by student to prepare theirself for entering prakerin at class XI of SMK N 6 Padang. Result of research which is conducted can be described as follows 1). Information is needed by student of SMK N 6 Padang about prakerin placed including to very important category with average percentage is 79% 2). ). Information is needed by student of SMK N 6 Padang about communication ways to prepare theirself for entering prakerin including to very important catergory with average percentage is 71%. According to research result can be concluded that the students need some information about prakerin. For that reason, it is expected that school can include prakerin information material on every subject.Â Â Â